PENGARUH DOSIS LIMBAH KULIT PISANG KEPOK SEBAGAI BAHAN UTAMA PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN MELON (Cucumis melo. L) SEBAGAI BAHAN PENYUSUN LKPD - Vironica, Elysa; Oka, Anak Agung; Sutanto, Agus (EDUBIOLOCK, 2025)
Kepok banana waste, which contains essential NPK nutrients, has the potential to enhance plant growth. This study investigated the effects of combining liquid organic fertilizer (POC) derived from Kepok banana waste with manure on the growth of melon plants (Cucumis melo L.), and identified the optimal dosage for growth performance. The outcomes of this research were further developed into a contextual learning resource in the form of student worksheets for biology education. The experiment was conducted using a Completely Randomized Design (CRD) with four treatments and five replications over a two-month period. Growth parameters observed included the number of branches, the number of flowers, and fresh fruit weight. Data were analyzed using the Kruskal–Wallis test. Results showed significant effects of the POC–manure combination across all parameters: number of branches (Hhit = 27.55 > χ²0.95;3 = 7.81), number of flowers (Hhit = 26.5 > χ²0.95;3 = 7.81), and fresh fruit weight (Hhit = 20.58 > χ²0.95;3 = 7.81). The best treatment for enhancing branch and flower production was P4, whereas P2 produced the greatest fruit weight. These findings confirm that POC from Kepok banana waste, when combined with manure, significantly improves melon plant growth. Furthermore, the study highlights the educational potential of integrating research results into biology learning through student worksheets, particularly for Grade XII on the topic of plant growth and development.